Managing Your Outsourced IT Services Provider: How to Unleash the Full Potential of Your Global Workforce - Upadrista, Venkatesh (Springer, 2015)
Managing Your Outsourced IT Services Provider teaches executives and managers of organizations how to unleash the full potential of their outsourced IT services workforce and IT-enabled business processes safely and profitably. Drawing on two decades of experience managing client relationships for global IT services companies, Venkatesh Upadrista guides outsourcing organizations around the hazards of geographic distance, linguistic miscommunication, organizational mismatch, and functional disparity between receiver requirements and provider capabilities.